2007
DOI: 10.1159/000103743
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Channel Antagonist MK-801 Does Not Protect against Bilirubin Neurotoxicity

Abstract: Background: Bilirubin encephalopathy or kernicterus is a potentially serious complication of neonatal hyperbilirubinemia. The mechanism of bilirubin-induced neurotoxicity is not known. Many neurological insults are mediated through NMDA receptor activation. Objective: We assessed the effect of the NMDA channel antagonist, MK-801 on bilirubin neurotoxicity in vivo and in vitro. Methods: Bilirubin toxic ity in vitro was assessed using trypan blue staining. Sulfadimethoxine injected (i.p.) jaundiced Gunn rat pups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 99 publications
2
9
1
Order By: Relevance
“…However, this did not occur with MK-801 glutamate NMDA receptor antagonist. This finding is in agreement with Shapiro et al [17] who found in hippocampal neurons and in Gunn rat pups that bilirubin neurotoxicity is not mediated through NMDA receptor activation. On the other hand, our results are in disagreement with Hankø et al [18] who demonstrated in NT2-N cells, a teratocarcinoma-derived cell line, that MK-801 can only delay UCB-induced cell death; and with Grojean et al [19] who found in primary forebrain neuronal cultures that MK-801 is protective against bilirubin-induced apoptosis and necrosis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, this did not occur with MK-801 glutamate NMDA receptor antagonist. This finding is in agreement with Shapiro et al [17] who found in hippocampal neurons and in Gunn rat pups that bilirubin neurotoxicity is not mediated through NMDA receptor activation. On the other hand, our results are in disagreement with Hankø et al [18] who demonstrated in NT2-N cells, a teratocarcinoma-derived cell line, that MK-801 can only delay UCB-induced cell death; and with Grojean et al [19] who found in primary forebrain neuronal cultures that MK-801 is protective against bilirubin-induced apoptosis and necrosis.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, our results are in disagreement with Hankø et al [18] who demonstrated in NT2-N cells, a teratocarcinoma-derived cell line, that MK-801 can only delay UCB-induced cell death; and with Grojean et al [19] who found in primary forebrain neuronal cultures that MK-801 is protective against bilirubin-induced apoptosis and necrosis. It is difficult to explain these different results, but one key difference between our study and that of Shapiro et al [17] and those demonstrating neuroprotection with MK-801 [18, 19] is that the former were performed in neuronal slices or cultures from hippocampi, whereas the latter were performed in teratocarcinoma-derived cell line [18] or embryonic cortical neurons [19]. In fact, in human and rat studies of bilirubin encephalopathy, the hippocampus has been shown to be affected, along with brainstem and the basal ganglia, while no injury has been demonstrated in the cortex [6].…”
Section: Discussioncontrasting
confidence: 89%
“…BAEPs were recorded using a Nicolet Spirit 2000 Evoked Potential System (Biosys, Inc.). The left ear was occluded with petrolatum, and BAEPs were obtained to monaural 100 μsecond duration rarefaction clicks delivered at 31.7/sec to the right ear through a Sony Walkman 4LIS headphone speaker (Shapiro, et al, 2007; Geiger, et al, 2007; Rice and Shapiro, 2006; Rice and Shapiro 2008). The sound intensity was nominally set at 70 dB, which corresponded to a level of about 62 dB above a normal jj Gunn rat pup BAEP threshold level (Rice and Shapiro, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…More consistent neurological sequelae can be produced in 16 day old jaundiced pups by administration of a compound that competes with bilirubin for binding to serum albumin resulting in bilirubin migrating out of the circulation and into lipophilic tissues, including the brain, to produce acute toxicity. Our laboratory typically uses sulfadimethoxine (sulfa) to produce acute bilirubin toxicity as demonstrated with BAEP abnormalities (Shapiro, 1988; Shapiro, 1993; Shapiro, et al, 2007; Geiger, et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of NMDA receptor antagonist MK-801 was shown to prevent the expression of nNOS, the consequent release of NO, the production of cyclic guanosine 3 ′ ,5 ′ -monophosphate (cGMP), as well as cell dysfunction and demise (Hankø et al, 2006a; Brito et al, 2010), but not the extracellular accumulation of glutamate in primary cultures of cortical neurons (Brito et al, 2010). Conflicting results were observed for MK-801 in hippocampal neurons treated with high UCB levels (Shapiro et al, 2007), not considered clinically relevant by surpassing UCB aqueous solubility (Ostrow et al, 2003b; Zhou et al, 2010), and in Gunn rats pups, where no protection against BAEPs abnormalities was observed (Shapiro et al, 2007). …”
Section: How Does Bilirubin Make Neurons Sick?mentioning
confidence: 99%